Phase 1 trial of carfilzomib in relapsed/refractory peripheral T-cell lymphoma - Krishnan, Mridula; Bociek, R. Gregory; Fanale, Michelle; Iyer, Swaminathan P.; Lechowicz, Mary Jo; Bierman, Philip J.; Armitage, James O.; Lunning, Matthew; Kallam, Avyakta; Vose, Julie M. (Annals of hematology, 2022)
Peripheral T-cell lymphomas (PTCL) are a unique subset of lymphomas with a poor prognosis due to limited treatment options. We performed a phase 1 study of carfilzomib in patients with relapsed/refractory PTCL to determine the safety profile and the maximum tolerated dose (MTD) of this agent. The study was a classical 3 + 3 phase 1 design with intra-patient dose escalation allowed beginning on day 8 of cycle 1 and subsequently. Dose-limiting toxicity (DLT) was defined as the occurrence of any grade 3/4 adverse event. Carfilzomib was given on days 1, 2, 8, 9, 15, and 16 of a 28-day cycle. Fifteen patients were enrolled from 3 centers. The median age of patients was 62. The median number of prior therapies for subjects on this trial was five. The MTD of carfilzomib was 36 mg/m 2 . Dose-limiting toxicities included anemia and sepsis. Serious adverse events were seen in 45% of patients. Single-agent carfilzomib leads to a complete response in one patient and a partial response in one patient. Overall, the drug was reasonably tolerated for a heavily pretreated population, but the limited response rate and short duration of response demonstrate a lack of promise for carfilzomib as a single agent in this patient population.